The Comparison Between Plyometrics and Aerobic Exercises toward Medical Students of Diponegoro University - Iin Atika Situngkir; Endang Ambarwati; Endang Kumaidah; Sumardi Widodo (Jurnal Kedokteran Diponegoro)
ABSTRACT